Finite strain pattern inferred from magnetic fabrics across the southern portion of the Central Range, Taiwan - Ya-Chu Tseng; En-Chao Yeh; Ning-Shan Hui; Yu-Min Chou; Jian-Cheng Lee; Ching-Chou Fu (Tectonophysics, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Eutrophication‐induced dinoflagellate succession contributes to marine carbon sequestration through refractory dissolved organic matter accumulation - Fu‐Tao Fang; Zhuo‐Yi Zhu; Yuan‐Bi Yi; Ding He; Hong‐Yan Bao; En‐Ren Zhang; Cheng‐Xu Zhou (Limnology and Oceanography, 2025)
The increasing eutrophication of coastal seas is causing a shift in the most important phytoplankton groups from diatoms to dinoflagellates, but its feedback to marine carbon cycling remains unclear. Here, we investigated the potential of the key coastal phytoplankton, the diatom Skeletonema costatum , and the dinoflagellate Prorocentrum donghaiense , for refractory dissolved organic carbon (DOC) accumulation over dark degradation incubations of 70 d. Our multi‐method approach showed that dinoflagellate detritus, rather than diatom detritus, significantly contributes to refractory DOC. This is evidenced by the fact that the detritus of dinoflagellates compared to that of diatoms (1) has a weaker transmittance in infrared spectrometry, indicating a lower content of labile organic substances (alcohol and amide groups); (2) has a higher release and/or transformation efficiency of particulate organic carbon to DOC (81% vs. 50%); (3) has a lower content of labile fraction, amino acid (8% vs. 17% carbon) and exhibits lower degradability of the DOC formed (23% vs. 30%); (4) has a lower content of labile compounds determined by Fourier transform ion cyclotron resonance mass spectrometry (maximum molecular lability boundary: 21% vs. 31%); and (5) has a higher proportion of refractory carboxylic‐rich alicyclic molecules (57% ± 0.5% vs. 51% ± 0.7%) over incubations. Our results emphasize that eutrophication‐triggered coastal dinoflagellate succession has a significant potential for positive feedback to carbon sequestration through the formation of refractory DOC.

Impact of future climate from different general circulation models on cotton yield predictions in north Cotton Belt through crop simulation with DSSAT - Mohil Pourebrahimi Foumani; Xinhua Yin; Joshua S. Fu; Cheng-En Yang; Regina Adotey (Field Crops Research, 2025)

A new diterpenoid alkaloid from the Aconitum scaposum - Cheng-En Fu; Gui-Fang Li; Guo-Qing Sun; Shuai Huang; Lin Chen; Xian-Li Zhou (Phytochemistry Letters, 2025)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Diterpenoid alkaloids with chemotaxonomic significance from Aconitum polycarpum - Lin Chen; Jie Wen; Jia-Yi Ma; Ke Xu; Cheng-En Fu; Wen-Cheng Liang; Chen-Ying Zhu; Jin-Qiu Wang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2024)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Constitutive expression of a plant ferredoxin-like protein (pflp) enhances capacity of photosynthetic carbon assimilation in rice (Oryza sativa) - Hsiang Chang; Hsiang-En Huang; Chin-Fu Cheng; Mei-Hsuan Ho; Mang-Jye Ger (Transgenic Research, 2017)

Effectiveness of SO2 emission control policy on power plants in the Yangtze River Delta, China—post-assessment of the 11th Five-Year Plan - Jiani Tan; Joshua S. Fu; Kan Huang; Cheng-En Yang; Guoshun Zhuang; Jian Sun (Environmental Science and Pollution Research, 2017)